Impact of baseline beta-blocker use on inotrope response and clinical outcomes in cardiogenic shock: a subgroup analysis of the DOREMI trial - Di Santo, Pietro; Mathew, Rebecca; Jung, Richard G.; Simard, Trevor; Skanes, Stephanie; Mao, Brennan; Ramirez, F. D.; Marbach, Jeffrey A.; Abdel-Razek, Omar; Motazedian, Pouya; Parlow, Simon; Boczar, Kevin E.; et al. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Cardiogenic shock (CS) is associated with significant morbidity and mortality. The impact of beta-blocker (BB) use on patients who develop CS remains unknown. We sought to evaluate the clinical outcomes and hemodynamic response profiles in patients treated with BB in the 24 h prior to the development of CS. Methods Patients with CS enrolled in the DObutamine compaREd to MIlrinone trial were analyzed. The primary outcome was a composite of all-cause mortality, resuscitated cardiac arrest, need for cardiac transplant or mechanical circulatory support, non-fatal myocardial infarction, transient ischemic attack or stroke, or initiation of renal replacement therapy. Secondary outcomes included the individual components of the primary composite and hemodynamic response profiles derived from pulmonary artery catheters. Results Among 192 participants, 93 patients (48%) had received BB therapy. The primary outcome occurred in 47 patients (51%) in the BB group and in 52 (53%) in the no BB group (RR 0.96; 95% CI 0.73–1.27; P = 0.78) throughout the in-hospital period. There were fewer early deaths in the BB group (RR 0.41; 95% CI 0.18–0.95; P = 0.03). There were no differences in other individual components of the primary outcome or in hemodynamic response between the two groups throughout the remainder of the hospitalization. Conclusions BB therapy in the 24 h preceding the development of CS did not negatively influence clinical outcomes or hemodynamic parameters. On the contrary, BB use was associated with fewer deaths in the early resuscitation period, suggesting a paradoxically protective effect in patients with CS. Trial registration ClinicalTrials.gov Identifier: NCT03207165